Memories of Starobielsk essays between art and history - Czapski, Józef 1896-1993 (New York Review Book, 2022)
"Interned with thousands of Polish army officers and a handful of civilians in the Soviet prisoner-of-war camp at Starobielsk in September 1939, the artist Józef Czapski was one of a very small number to survive the massacre carried out in the forest of Katyn in April 1940. In prose written while the war still raged, Czapski portrays these doomed men, some with the detail of a finished portrait and others in vivid sketches imbued with a rare combination of intimacy and respect, registering their fierce striving to remain fully engaged in humane pursuits under hopeless circumstances. This memoir is complemented by essays on art, history, and literature that show Czapski's lifelong attachment to the Russian culture that educated him, in all its contradictory manifestations, from the poet Aleksandr Blok's fascinated response to revolution to the lonely struggle of the painter Chaim Soutine. They include a wartime sequence of short essays on painting written on a train when Czapski was traveling from Moscow to the Second Polish Army's strategic base in Central Asia, which are among his most lyrical and insightful reflections on art."
Translated from the Polish
Keywords: Czapski, Józef -- 1896-1993; Kriegsgefangenenlager Starobelsk; Geschichte; Geschichte 1939-1940; Polnischer Kriegsgefangener; Kunst; Literatur; Russland; Czapski, Józef / 1896-1993; Starobilʹsʹk (Ukraine : Concentration camp); Arts; Erlebnisbericht; Aufsatzsammlung